Trust and monitoring - Simon Lesmeister; Peter Limbach; Marc Goergen (University of Cologne, Centre for Financial Research (CFR), 2022)
We show that in countries with more societal trust shareholders cast fewer votes at shareholder meetings and are more supportive of management proposals. This result is confirmed by instrumental variable regressions. It also holds at the U.S.-county level and for voting by U.S. institutional investors. Lower monitoring via voting relates less negatively to future firm performance in high-trust countries, suggesting that managers do not exploit greater discretion when trust is high. We also find a negative relation between trust and bond spreads. Our evidence supports theory arguing that trust substitutes for monitoring and has implications for investors' optimal monitoring effort.
Keywords: G3; G19; G32; 330; Culture; Monitoring; Shareholder expropriation; Shareholder voting; Societal trust